Short stay total joint arthroplasty program: patient factors predicting readmission - Lalonde, Sebastien (Can J Surg, 2019)
BACKGROUND: The aim of this study was to evaluate the effectiveness of our short stay arthroplasty program as measured by 30-day readmission rate and the rate of transfer to inpatient care. Risk factors for readmission/transfer were also evaluated and contrasted with current patient screening criteria. METHODS: We retrospectively reviewed 297 charts for all primary total joint arthroplasties completed in the short stay program during an 18-month period. Data included readmission and patient characteristics such as age, sex, comorbidities, the American Society of Anesthesiologists (ASA) physical classification grade, body mass index (BMI) and the number of preoperative medications. RESULTS: The 30-day readmission rate was 2.6% (n = 8). With the inclusion of patients transferred to the inpatient hospital, the overall failure rate of our short stay program was 6.7% (n = 20). Multivariable modelling controlling for age, BMI and ASA suggested that those with an in-hospital complication were 11.4 times more likely to be readmitted or transferred to inpatient care (p < 0.001) with a trend for patients who were taking more medications (p = 0.09). CONCLUSION: The current readmission rate from this program is comparable to previously published data in the arthroplasty literature. However, several patients required transfer to inpatient care, which significantly impacted the effectiveness of the short stay program. Risk factors for readmission/transfer are not completely accounted for by current presurgical screening criteria. Further evaluation of the Blaylock Risk Assessment Screening Score is required to determine its value for predicting hospital readmission.